Corporate Social Responsibility & Twitter: The Power & Potential of 140 Characters - Brar, Navreet (2011)
This study examines the extent to which Canada’s leading companies in the CSR sphere utilize social media, and specifically, the service Twitter, to engage in dialogue with stakeholders. The research is performed in an environment supported by a review of literature spanning several business domains. Through a qualitative research approach, augmented by case studies of six corporations, we contribute to understanding the social media and CSR relationship and are able to provide recommendations on how this relationship can be nurtured to evolve into one that is grounded in strategic CSR, enhancing the sustainable competitive advantage of the firm.